Microfluidic Devices in Fabricating Nano or Micromaterials for Biomedical Applications. Issue 12 (21st October 2019) - Luo, Xuan; Su, Peng; Zhang, Wei; Raston, Colin L.
Abstract: Nano or microsized particles have been a research focus for decades, and the advancement of microfluidic technologies provides alternative strategies for the synthesis of such materials for various applications. Recent advances of using different microfluidic devices (MDs), including continuous laminar flow, segmented flow, droplet‐based, and other non‐chip‐based microreactors, for the synthesis of nano or microsized particles with specific properties are reviewed, along with their biomedical applications. Different categories of particles fabricated in MDs are summarized to highlight the wide application of the processing platform in the development of novel functional materials. Abstract : Recent advances of using different microfluidic devices (MDs), such as chip‐based, tubular, or centrifugal microfluidics, for the synthesis of nano or microsized particles with specific properties are reviewed, along with their biomedical applications. Diverse particles are fabricated in MDs with defined morphology and homogeneity highlighting the wide application of the platform relative to batch processing.